Comparison between plant fossil assemblages and simulated biomes across the Permian-Triassic Boundary - Ragon, Charline; Vérard, Christian; Kasparian, Jérôme; Nowak, Hendrik; Kustatscher, Evelyn; Brunetti, Maura (Frontiers in Earth Science, 2025)
Terrestrial ecosystems underwent extreme shifts in composition, following extensive degassing associated with the Siberian Traps near the Permian–Triassic boundary (PTB). These climatic perturbations are recorded in land plant macrofossil assemblages, which reflect complex changes in major biomes at the stage level. In this study, we quantitatively compare the major biomes reconstructed from the plant macrofossil assemblage data with those derived from coupled climate–vegetation simulations across the PTB. We focus on five stages across the PTB, from the Wuchiapingian to the Anisian. Our findings indicate that a shift from a cold climatic state to one with a mean surface temperature approximately 10°C higher is consistent with observed changes over time in plant biomes, as documented in macrofossil records. In contrast, vegetation patterns during the Induan stage suggest strong variability, precluding a univocal attribution to a stable climate.